Synthesis of Zinc Oxide Nanoparticles from Medicinal Herb Bryophyllum pinnatum - Pravin R. Jadhav; Dhanashree K. Tarade; Kajal S. Tarade; Sakshi S. Kadam; Sushma S. Desai (The Bioscan, 2025)
Zinc oxide nanoparticles (ZnO NPs) have attracted considerable attention in several sectors, including medical and health technology, and environmental science, due to their unique properties consisting of a huge surface area, biocompatibility, and antimicrobial activity. This study aims to synthesize ZnO nanoparticles using a green, eco-friendly approach by employing Bryophyllum pinnatum, a widely known medicinal herb, as a naturally occurring stabilizing and reducing agent. Bryophyllum pinnatum is a prospective option for the synthesis of nanoparticles because of its many medicinal uses in traditional medicine, which include anti-inflammatory, antibacterial, and antioxidant activities. Under carefully monitored circumstances, an aqueous extract of Bryophyllum pinnatum was combined with a zinc salt precursor (zinc acetate) to create ZnO NPs. scanning electron microscopy (SEM), X-ray diffraction (XRD), and UV-visible spectrophotometry were used to track the reduction of zinc ions and the creation of ZnO nanoparticles. The ZnO NPs' hexagonal structure, as revealed by XRD analysis, is in line with ZnO's known crystal structure. With an average size range of 20–50 nm, the nanoparticles' spherical and evenly distributed shape was revealed by SEM analysis. These dimensions are in line with those of ZnO nanoparticles produced using environmentally friendly techniques. Significant antibacterial action against a range of bacterial strains was shown by the produced ZnO nanoparticles, indicating their potential for usage in medical applications such infection control and wound healing. The ZnO NPs' potential for therapeutic uses was further increased by antioxidant testing that revealed significant free radical scavenging activity. To sum up, this study demonstrates the ecologically friendly production of ZnO nanoparticles utilizing Bryophyllum pinnatum, offering a substitute for traditional chemical synthesis techniques. The biosynthesized ZnO NPs demonstrated advantageous traits for biomedical uses.